Analisis Pertumbuhan dan Optimalisasi Penerimaan Pajak Restoran di Kabupaten Sambas - Afriana, Ulfa’Izah Nur; Mukaromah, Lailatul; Sentiya, Novi; Munandar, Munandar (Indonesian Accounting Literacy Journal, 2025)
Restaurant taxes in Sambas Regency show great potential with a continuously increasing revenue trend that surpasses targets from 2020 to 2024. This study aims to analyze the growth and optimization of restaurant tax revenue in the area. Data was obtained through interviews with officials from the Regional Financial Agency (BAKEUDA) of Sambas Regency, restaurant taxpayers (WP), and tax consultants. The research results indicate that the growth of restaurant tax revenue is driven by the increasing number of new restaurants, an effectiveness of collection that reaches an average of 135.83% (very effective), as well the implementation of technology such as the Mobile Payment Online System (M-POS) and Tapping Box. Researchers recommend that BAKEUDA increase socialization and technical guidance on the use of M-POS and Tapping Box, as well as conduct systematic data collection on small businesses such as coffee shops to support the optimization of restaurant tax revenue.